Investigation of ochratoxin A in air-dry-cured hams - Toman, Jakub; Pickova, Darina; Rejman, Lukas; Ostry, Vladimir; Malir, Frantisek (Meat science, 2024)
The European Union legislation regarding ochratoxin A (OTA) in various foodstuffs has changed relatively recently. Nevertheless, the legislation does not regulate OTA in any meat and meat-derived products. In this legislation update, the European Commission requested new studies, including, besides others, the presence of OTA in hams, which raises the concern that its consumption may pose a potential risk of exposure to OTA. This study aims to investigate OTA in a total of 195 samples of air-dry-cured hams acquired at the Czech market from January to June 2023. The analytical technique of high-performance liquid chromatography in combination with a fluorescence detector with pre-treatment employing immunoaffinity columns was used to determine OTA. OTA was found in 93 (48%) samples of air-dry-cured ham, with the OTA concentration reaching up to 14.58 ng/g. Due to the current absence of regulation limits, the results of this study were compared with the Italian maximum limit of 1 ng/g regulating OTA in porcine meat and byproducts. The Italian OTA maximum limit was exceeded in 22 (11%) samples. This study shows that the population of the Czech Republic is exposed to OTA from this pork byproduct. It is essential to set an OTA regulatory limit for meat and food produced from it to protect human health.
Keywords: Ochratoxins; Chromatography, High Pressure Liquid; Food safety; Pork Meat; Nephrotoxicity; vepřové maso; HPLC-FD; masné výrobky; Mycotoxins; zvířata; ochratoxiny; Swine; kontaminace potravin; Food Contamination; Czech Republic; Immunoaffinity columns; Animals; Meat Products; Česká republika; vysokoúčinná kapalinová chromatografie; prasata